COHERENT GAMMA OSCILLATIONS COUPLE THE AMYGDALA AND STRIATUM DURING LEARNING - Popescu, Andrei T. (2009)
The basolateral amygdala (BLA) mediates the facilitating effects of emotions on memory. The BLA enhancing influence extends to various types of memories, including striatal–dependent habit formation. To shed light on the underlying mechanisms, we performed unit and local field potentials (LFP) recordings in BLA, striatum, auditory cortex, and intralaminar thalamus in cats trained on a stimulus-response task where the presentation of one of two tones (CS+) predicted reward delivery. The coherence of BLA but not cortical or thalamic LFPs was highest with striatal gamma activity and intra-BLA muscimol infusions selectively reduced striatal gamma power. Moreover, coupling of BLA-striatal unit activity increased when LFP gamma power augmented. Early in training, the CS+ and unrewarded tone elicited a modest increase in coherent BLA-striatal gamma. As learning progressed, this gamma coupling selectively increased in relation to the CS+. Thus, coherent gamma oscillations coordinate amygdalostriatal interactions during learning and might facilitate synaptic plasticity.